The Influence of Transformational Leadership and Organizational Culture on Public Service Quality Through Innovation at the Transportation Agency of West Tanjung Jabung Regency - Nurhamdi, Nurhamdi; Bukit, Pantun; Akbar, Ali (Journal of Accounting and Finance Management, 2025)
This study aims to determine and describe transformational leadership, organizational culture, innovation and quality of public services in the Transportation Agency of West Tanjung Jabung Regency, as well as to determine and analyze the influence of transformational leadership and organizational culture through innovation on the quality of public services in the Transportation Agency of West Tanjung Jabung Regency. This study was conducted at the Transportation Agency of West Tanjung Jabung Regency. The population is the community who receive service benefits from the Transportation Agency of West Tanjung Jabung Regency based on Counter, Route and Vehicle data of 290 people, while the sample size in this study uses Slovin theory with a margin of error of 10% so that 75 people are obtained. This study uses a quantitative approach with a survey method and uses Partial Least Square (PLS) data analysis. The results of the study indicate that transformational leadership and organizational culture have been proven to influence service quality, both directly and through innovation. Directly, leaders who are able to provide inspiration, motivation, and clear direction encourage employees to work more optimally, while a strong organizational culture forms a positive and service-oriented work attitude. Indirectly, both encourage innovation, such as new ideas, updated procedures, and the use of technology, which makes service faster, more effective, and more satisfying. This demonstrates that innovation is a crucial link between leadership, organizational culture, and improved service quality.